Aerodynamic investigation of biplanar wing configuration - Tieo, Jing Jin. (2012)
Biplanar wing configurations have characterised aircraft designs in the early days of aviation as structural limitations inhibited the widespread use of modern cantilevered monoplane wings. However, by the 1930s, improvements to structural technology and the advent of higher speed aircraft lead to the decline in the use of biplane designs. In recent years, research into micro aerial vehicle (MAV) design has led to renewed interests in the field of biplane aerodynamics. Such endeavours are driven by the need to improve the lifting performance of MAV wings which are subjected to significant constraints in its physical dimensions, most notably to the wingspan.